Dimethacrylate polymers with different glycerol content: Thermal study, degree of conversion, and morphological features - Alarcon, Rafael Turra [UNESP]; Gaglieri, Caroline [UNESP]; Bannach, Gilbert [UNESP] (Springer Nature, 2018)
The objectives of this study were to verify thermal properties, degree of conversion, and morphological features of several dimethacrylate polymers with different glycerol content and obtain the better proportion system to decrease cost of final polymer. These polymers were synthesized by photopolymerization, which has economic and ecological advantages. The glycerol can be used as a coinitiator in photopolymerization and has the advantage of being inexpensive and non-toxic; thus, it is in the scope of the green chemistry principles. Simultaneous thermogravimetry–differential thermal analysis and derivative thermogravimetric, differential scanning calorimetry, middle infrared spectroscopy, and scanning electronic microscopy were used to determine thermal properties, degree of conversion, and morphological characteristics of polymers obtained. The thermoanalytical results showed that glycerol addition in the dimethacrylate system caused few modifications in the thermal stability of the polymer and thermal events when compared with pure polymers (without glycerol). Two dimethacrylate systems (UDMA/glycerol and Bis-GMA/glycerol) showed good results for conversion degree and morphological aspects when compared with pure systems.
Keywords: Conversion degree; Dimethacrylates; Glycerol; Photopolymerization; Thermal analysis